Sustainability of a Social Business: A Case Study on Grameen Danone Foods Limited - Yasmin, Nur Nahar (Asian Business Review, 2016)
Achieving sustainability in the context of economic, social and environmental aspects has been one of the main focuses of modern times. The aim is to create the world that will facilitate the upcoming generations to lead a safe and sound life. Social business is a relatively new concept that assists in the creation of such a sustainable world by promoting and following the notion of “no-loss, no-dividend” business instead of conventional profit-maximizing business. The purpose of this paper is to show whether a social business can become a sustainable business and achieve the sustainable development goals set by United Nations. To scrutinize this theory of social business for sustainable development the author has selected Grameen-Danone Foods Limited (GDFL) as a case study. The endeavor of this paper is to elaborate the relationship between social business and sustainable development, describe GDFL as a social business and analyze the success (or failure) of GDFL as a sustainable social business. Finally, it tries to showcase a comparison of few of the sustainable development goals and the outcomes of the analysis of the business and social goals of GDFL. JEL Classifications: M 10